2019
DOI: 10.15369/sujms.31.29
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of <i>Polypodium Leucotomos</i> Extract on Cytochrome P450 3A-mediated Midazolam Metabolism

Abstract: Polypodium leucotomos PL is a fern native to Latin America, and its extract is used as an oral sunscreen ; however, its safety during use has not been adequately investigated. Therefore, the aim of this study was to evaluate fooddrug interactions associated with PL extract mediated by cytochrome P450 3A CYP3A inhibition and induction. Inhibition of CYP3A-mediated midazolam MDZ 1-hydroxylation activity by PL extract and its major phenolic components was evaluated in vitro using pooled human liver microsomes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
0
8
1
Order By: Relevance
“…Based on the findings of previous in vitro studies, the results of this study were unexpected. We previously reported that the PL extract competitively inhibits midazolam metabolism in human liver microsomes, 11 and predicted a similar effect in vivo.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Based on the findings of previous in vitro studies, the results of this study were unexpected. We previously reported that the PL extract competitively inhibits midazolam metabolism in human liver microsomes, 11 and predicted a similar effect in vivo.…”
Section: Discussionmentioning
confidence: 57%
“…Previously, we reported that 1-week treatment with PL extract results in no significant changes in the pharmacokinetics of midazolam in rats. 11 However, in the subsequent studies, the expression of CYP3A9 mRNA in the small intestine was found to be significantly increased (59%) by PL extract treatment, indicating the induction and/or activation of small intestinal CYP3A9 in rats (Nishimura, Y., unpublished data). As CYP3A4 is involved in the metabolism of many drugs, long-term use of the PL extract would increase the opportunities for its concomitant use with drugs that are metabolized by this enzyme.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…As described above, IBM Micromedex generated no results for drug–drug interactions, and most reviews addressing polypodium leucotomos’ safety profile did not describe drug interactions 22 . A study in animal models observed P450 CYP3A inhibition by polypodium leucotomos in mice dosed with midazolam 23 . This may warrant caution in patients using CYP3A metabolized drugs with narrow therapeutic indexes, including tacrolimus, the drug levels of which are especially important to maintain in transplant patients 24 .…”
Section: Literature Reviewmentioning
confidence: 99%